Review and Comparison of Four-Tier Multiple Choice and Five-Tier Multiple Choice Diagnostic Tests to Identify Mastery of Physics Concepts - Hendra Musfa Dirman; Fatni Mufit; Festiyed Festiyed (Postgraduate, University of Mataram, 2022)
Misconceptions of a concept in a lesson will have an influence on understanding the next concept. Having misconceptions that exist in learning can understand the nature of the misconceptions and consequently can help student learning progress. Therefore, a diagnostic test for misconceptions is needed, including the newest four-tier multiple-choice and five-tier multiple-choice. This research is a literature review that provides an information system using the PRISMA method which often occurs in students' misconceptions in high school physics subjects. The data for this research are 60 selected articles from 2017-2021. The purpose of this study is to reveal the use of four-tier multiple-choice and five-tier multiple-choice diagnostic tests in physics and also provide a comparison of each instrument with the strengths and weaknesses of the four-tier multiple-choice and five-tier multiple-choice diagnostic tests. Furthermore, the use of multiple-choice four levels (83.33%) and multiple-choice five levels (16.67%). In the use of the four-tier multiple choice physical material diagnostic test, which is often used in identifying misconceptions, are optical devices (12%) and energy businesses (10%). And the use of an additional five-tier multiple-choice instrument diagnostic test that is often used is to present an overview or conclusion at the fifth level. However, each type of four-tier multiple-choice and five-tier multiple-choice test has its own advantages and disadvantages in assessing students' conceptions.